Strategi Guru Pendidikan Agama Islam Dalam Menanamkan Karakter Religius Pada Peserta Didik Di SMP IT Wahdah Islamiyah Makassar - Rajemma Rajemma; Andi Abd Muis (Journal of Humanities, Social Sciences, and Education, 2025)
Instilling religious character is a crucial aspect in Islamic education, especially at the Junior High School level. This study aims to reveal the strategies implemented by Islamic Religious Education (PAI) teachers in instilling religious character in students at SMP IT Wahdah Islamiyah Makassar. This study uses a qualitative approach with a case study type. Data collection was carried out through observation, in-depth interviews, and documentation. The research informants were PAI teachers, principals, and students. The results of the study showed that PAI teachers implemented several main strategies, namely: (1) role models in daily religious behavior, (2) habituation of worship such as congregational prayer, reading the Qur'an, and morning dhikr, (3) integration of Islamic values ​​in all subjects, and (4) providing motivation and rewards for students' religious behavior. This strategy is supported by an Islamic school environment and parental involvement in fostering children's morals at home. Instilling religious character is not only done formally through classroom learning, but also through extracurricular activities and routine coaching. With this strategy, students' religious character can grow consistently and continuously. This study recommends strengthening collaboration between teachers, parents, and schools so that the formation of religious character is more optimal.